The Effect of Profitability, Capital Structure, and Good Corporate Governance on Financial Performance of Property and Real Estate Companies Listed on The Indonesia Stock Exchange (IDX) in 2020–2023 - Kristin Monica Br Sembiring; F.X. Kurniawan Tjakrawala (Edunity Kajian Ilmu Sosial dan Pendidikan, 2025)
This research seeks to examine and evaluate the influence of Profitability (measured by Return on Assets/ROA), Capital Structure (measured by Debt to Equity Ratio/DER), and Good Corporate Governance (measured by the Board of Directors) on the Price to Earnings Ratio (PER) among property and real estate firms listed on the Indonesia Stock Exchange (IDX). Employing a quantitative research approach, the study focused on companies listed between 2020 and 2023, totaling 94 firms. After applying specific selection criteria, a sample of 44 companies was obtained for analysis. Panel data regression using EViews software was utilized to process the data. The findings reveal that profitability, as indicated by ROA, has a positive and statistically significant impact on financial performance, represented by PER. Conversely, DER was found to have no significant influence, while the Board of Directors demonstrated a negative and significant effect on PER. These results are specific to the property and real estate sector listed on the IDX.